2005
DOI: 10.1002/eji.200526262
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia suppresses the production of matrix metalloproteinases and the migration of humanmonocyte‐derived dendritic cells

Abstract: As most solid tumors are hypoxic, dendritic cells (DC) in solid tumors are also exposed to hypoxia. While many adaptation responses of tumor cells to hypoxia are known, it is yet to be determined how hypoxia affects the functions of DC. To explore the effects of hypoxia on the functions of DC, we compared the expression of surface markers, cytokines, chemokine receptors and matrix metalloproteinases (MMP) of human monocyte-derived DC (hmDC) differentiated under hypoxia to those differentiated under normoxia. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
31
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 38 publications
9
31
1
Order By: Relevance
“…It was reported that hypoxia inhibited the migratory capacity of DCs through extracellular matrix by reducing matrix metalloproteinase-9 expression and augmenting the protease inhibitor tissue inhibitor of metalloproteinase 1 (51,52). We observed that there is no intrinsic defect in the migration of Hi-DCs, which respond more than iDCs to an appropriate stimulus in the absence of an extracellular matrix barrier as it occurs in the Transwell assay.…”
Section: Hypoxia and Differentiation Of Dendritic Cells Mol Cancer Resupporting
confidence: 46%
“…It was reported that hypoxia inhibited the migratory capacity of DCs through extracellular matrix by reducing matrix metalloproteinase-9 expression and augmenting the protease inhibitor tissue inhibitor of metalloproteinase 1 (51,52). We observed that there is no intrinsic defect in the migration of Hi-DCs, which respond more than iDCs to an appropriate stimulus in the absence of an extracellular matrix barrier as it occurs in the Transwell assay.…”
Section: Hypoxia and Differentiation Of Dendritic Cells Mol Cancer Resupporting
confidence: 46%
“…Our results contribute to explain the controversial findings in the literature concerning the effect of hypoxia on MMP-9 levels. MMP-9 production was shown to be downregulated by hypoxia in human monocyte-derived dendritic cells 49 but upregulated in both tumoral 50 and cardiac muscle cells. 51 Both Pyk2 phosphorylation 52 and ROS 53 may underlie the ability of hypoxia to activate NF-κβ.…”
Section: Discussionmentioning
confidence: 98%
“…The potentially important impact of the local oxygen tension in inflamed tissues on DC regulation is still largely unknown. Two reports (8,9) suggested a reduced migratory capacity of human monocyte-derived DC differentiated under hypoxia, but further evidence for functional effects of hypoxia on DC biology is lacking to date. In particular, the effect of hypoxia on the capability of DC to induce immune responses has not been analyzed yet.…”
Section: Endritic Cells (Dc)mentioning
confidence: 99%